Centro de apoyo académico para niños en etapa escolar abc - León, Wendy (2010)
Nowadays thousands of hard-working parents in Ecuador face the need to possess help specialized for the care of his children and support for the accomplishment of his school tasks, but at the same time they know that a simple vigilance is not sufficient. The major children have different needs that those who are in maternally or pre-school, since they need from a tutor that it advises them in the academic questions, as well as to take part in different activities that stimulate his capacities and skills. In this work there appears the development of the creation of The Center of Academic Support For Children In School Stage ABC, which has as end replace this need of the parents giving academic support with forecast of tasks and activities for the recreation and enrichment by means of the exposition of aims, investigation of market and marketing plan, as well as the production of the following studies: technician, organizational and financier.